Gene expression of interleukin 18 in unstimulated peripheral blood mononuclear cells of patients with alcoholic cirrhosis - Hanck, Christoph; Manigold, Tobias; Böcker, Ulrich; Kurimoto, Masashi; Kölbel, Christian Berthold; Singer, Manfred V.; Rossol, Siegbert (Gut, 2001)
BACKGROUND Most patients with alcohol induced cirrhosis (AC) and chronic endotoxinaemia are not suffering from clinically evident systemic inflammatory reactions. This may be due to altered gene expression of cytokines, possibly related to endotoxin (for example, tolerance and sensitisation). Interleukin 18 (IL-18; interleukin γ inducing factor) modulates local cytokine production in response to endotoxin (lipopolysaccharide (LPS)). - AIM To investigate the systemic immune response of patients with AC and to see if unstimulated peripheral blood mononuclear cells (PBMC) from patients with AC are activated and contribute to gene expression of IL-18. - METHODS Plasma levels of endotoxin (LPS) and serum levels of IL-18 were measured by enzyme linked immunoassay and the amoebocyte lysate test in 74 abstinent patients with different stages of AC (Child-Pugh stage A, n=18; B, n=22; C, n=34) and compared with healthy controls (n=43). Gene expression of IL-18 was assessed by semiquantitative reverse transcription-polymerase chain reaction in freshly isolated unstimulated PBMC of a subgroup of 14 patients with AC compared with five healthy controls. - RESULTS Gene expression of IL-18 specific mRNA in unstimulated PBMC was significantly enhanced in patients with advanced AC (Child-Pugh stage C) and correlated with plasma LPS and serum CD14 levels (Spearman rank correlation factors r=0.76 andr=0.72). Serum concentrations of IL-18 were also elevated compared with healthy controls (p<0.001) but correlation with serum levels of CD14 and plasma levels of LPS was much weaker compared with mRNA data (Spearman rank correlation factorsr=0.47 andr=0.26). - CONCLUSIONS Our in vivo data suggest a presensitisation of “unstimulated” PBMC in the circulation of patients with AC by endotoxin. The term “unstimulated” may be inadequate in patients with AC. Further investigations are needed to define the exact mechanisms and localisation of sensitisation of PBMC in vivo.